Saliva Sampling for Prospective SARS-CoV-2 Screening of Healthcare Professionals - Raimann, Adalbert; Farr, Alex; Huscsava, Mercedes; Krois, Wilfried; Strassl, Robert; Schellnegger, Julia; Eibensteiner, Fabian; Göschl, Bernadette; Schned, Hannah; Steinbauer, Philipp; Hetzmannseder, Mathias; Stiegner, Fabian; et al. (Frontiers in Medicine, 2022)
OBJECTIVE The objective of this study was to analyze the feasibility and acceptance of a non-invasive, daily and proactive screening program for SARS-CoV-2 infection employing serial saliva testing, in combination with a digital questionnaire among healthcare providers (HCPs) in a multi-professional setting. DESIGN This was a prospective cohort study involving HCPs from different units at a single tertiary care center, over a pilot phase of four weeks during the first wave of the COVID-19 pandemic from April 18th to June 6th, 2020. SETTING Pediatric tertiary patient care units, Comprehensive Center for Pediatrics, Medical University of Vienna. SUBJECTS HCPs from different units, including physicians, nurses, midwives, and administrative staff (with patient contact) were considered eligible for the study. Study participants were working in different settings in our center at varying levels of risk exposure. INTERVENTIONS Saliva collection from mouth gargle and electronic symptom and exposure monitoring (eSEM) was performed by participants at the onset of each regular clinical shift (day or night shift), using an anonymous ID for matching the results. MEASUREMENTS RT-PCR of all saliva samples, eSEM, as well as feasibility and acceptance thereof. RESULTS 275 volunteers collected 1,865 saliva samples and responded 1,378 times in the eSEM during a four-week period. 1,331 (96.7%) responses were that the testing was feasible and acceptable. The most common severe symptom during the four-week period mentioned by HCPs was headache, reported 54 times (3.9%). Two SARS-CoV-2 positive samples - one of them being associated with symptoms - were identified. The acceptance rate among HCPs was 96.6%. CONCLUSION Serial saliva screening was a well-accepted and feasible method for monitoring SARS-CoV-2 infectious state in health care professionals. Combination of regular SARS-CoV-2 tests with sequential saliva collection and storage could potentially represent a highly efficient strategy to identify and trace virus positive staff for employee and patient safety.